THE MECHANISM OF THE EFFICIENCY ENSURE INTERACTION OF AIR TRANSPORT SERVICES - Borysenko, O. S. (Science and Transport Progress, 2009)
In the article the mechanism of co-operation of the airline with the subjects of external environment is substantiated and it is defined that exactly on the basis of corporate relations at combination of three managing subjects and determination of their unique economic interests the process of intercommunication on providing of effectiveness of air transport service is provided.